Efektivitas Bahan AjarBuku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Terhadap Peningkatan Pengetahuan Bencana Gempa Bumi Melalui Strategi Numberel Heads Together Di SMK Muhammadiyah 2 Klaten - Chasanah, Dyah, Drs. Rubino Rubiyanto, M. Pd (2016)
National Disaster Mitigation Agency has been relase module of disasters in Klaten District and that module will be an object the author to test how much effective for Tim Mitigation Disasters in SMK Muhammadiyah 2 Klaten. More less 40 student in SMK Muhammadiya 2 Klaten who follow mitigation tim. The authir using Numbered Heads Together to simpifly the students for accept materials of earthquake and mitigation. This research is a kind of experiment research with true experimental design. In this reseach who does by extra experimental tim is divide by two groups , the first group is experimental class. And the rating percentage is 78,53% for the pre testand 87,26% for the post test. Value of the pre test is less than post test because when the pre test, the student didnt know the materials about mitigations. The experimen class has been improve the knowladge after given handling with NHT strategy. Total value of averege pre test controling class is 75,3 and the post test is 81,2. Result of pre test and the post test increased by 5,9%. So its been increase the effectiveness module of disaster to grade knowladge participans in SMK Muhammadiyah 2 Klaten. Using NHT Strategy can reach the purpose of the study, this is proved with increasing average of the post test beetwen experiment class and controling class. Key Words: Teaching materials, effectiveness, earth quake, Numbered Heads Together.